The Influence Of Bookzi Media And Lecture Method On Knowledge And Attitude Towards Balanced Nutrition: A Study On Fifth Grade Students Of Sdn 01 Mangga Dua Selatan Jakarta - Putri, Vira Herliana; Paramarta, Vip; Rahmiyati, Ayu Laili (Jurnal Manajemen Bisnis, 2026)
School aged children are a vulnerable group to nutritional problems that may affect growth, cognitive development, and skills. One major contributing factor is inadequate knowledge of balanced nutrition. This study aimed to examine the differences and effects of Bookzi media and lecture methods on students’ knowledge and attitudes toward balanced nutrition among fifth-grade students at SDN 01 Mangga Dua Selatan. A quantitative approach with a quasi-experimental design was applied. The population consisted of 116 students, with 56 respondents selected using purposive sampling. Data were analyzed using t-tests and F-tests with SPSS software. The results showed that both Bookzi media and lecture methods had significant partial effects on improving knowledge and attitudes toward balanced nutrition (p<0.05). Simultaneously, both methods significantly influenced all post-test variables (p=0.000). However, the increase in knowledge and attitude scores was higher in the Bookzi group than in the lecture group. These findings indicate that edutainment-based educational media are more effective in enhancing students’ understanding and fostering positive attitudes toward balanced nutrition.